Linomotion: reviving traditional prints with AR in the era of digital madani - Oscar Gordon Wong; Cristhiee Shenna Chin (Akademi Seni dan Teknologi Kreatif, Universiti Malaysia Sabah, 2024)
LinoMotion is an innovative product that combines traditional lino print art and augmented reality (AR) technology, which aligns with Malaysia's Digital Madani aspiration to bridge cultural heritage towards the digital age. An AR scanner in the audience's phone scans the lino print, and they can see a scene of animated lino print characters moving about through a virtual space. The AR algorithms detect and animate each lino print's designs, giving us this incredible dynamic visual. Users have the ability to engage with the animated motion of the lino print art, while also generating a presentation of the lino infographic material. These interactive results facilitate viewer's comprehension of the lino artwork they are observing. The combination of AR with lino printing bridges the gap between traditional art and modern technology to create an interactive learning experience that will attract people to appreciate arts again.